TechMaps: exploring technology relationships through patent information based proximity - Perez-Molina, Eduardo; Loizides, Fernando (Frontiers in research metrics and analytics, 2023)
Our work provides a novel method for rich information discovery about the evolution of technical fields and company developments through patent relationships. A new exploratory method and graphical tool to discover technology proximity based on patent classification information are introduced. By technology we mean a technical field (defined by an International Patent Classification—IPC—code or a combination of them) or an organization (such as a tech company, research center, or institution). A single data structure is used for characterizing both technical fields and organizations, to visualize them as items of the very same body. This new method generates two graphs: the first graph, the TechnologyMap , visualizes technology items in a 2D plot wherein technical fields and companies will appear positioned relative to each other; the. A second graph, the Focused TechnologyMap , visualizes technology items with respect to a selected one, the focus , which is located in the center of a circle whose radii correspond to the complete set of IPC codes. This article represents the process and algorithms used for production of the graphs, and solidifies the assumptions of validity by presenting two of the many successful test cases to which it was applied.